Społeczne wskaźniki zrównoważonego rozwoju - Borys, Tadeusz; Markowska, Małgorzata (Social Indicators of Sustainable Development, 2005)
In this article the sustainable development is interpreted as an integrated order, in which substantial role - apart from economic and environmental order - is played by the social order. The main objective of the study is to identify social indicators of sustainable development. It presents Polish experiences in elaborating sets of these indicators on the country level, at the background of other European Union countries, but also in the context of monitoring by means of indicators, being created right now for two basic, strategic documents of the European Union: the Lisbon Strategy and the EU Sustainable Development Strategy. There are also presented selected social indicators of sustainable development for the European Union countries. The performed comparative analysis referring to space and time presents the position of Poland with reference to other countries, the mean values for the EU-15, before the accession and the mean values for the European Union in its present shape (25 countries).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 71-78